2020
DOI: 10.3390/rs12081332
|View full text |Cite
|
Sign up to set email alerts
|

Revealing the Fingerprint of Climate Change in Interannual NDVI Variability among Biomes in Inner Mongolia, China

Abstract: An understanding of the response of interannual vegetation variations to climate change is critical for the future projection of ecosystem processes and developing effective coping strategies. In this study, the spatial pattern of interannual variability in the growing season normalized difference vegetation index (NDVI) for different biomes and its relationships with climate variables were investigated in Inner Mongolia during 1982-2015 by jointly using linear regression, geographical detector, and geographic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 53 publications
2
18
0
Order By: Relevance
“…In addition, our results also showed that the greening pixels were located mainly in the northeast and southwest, whereas central and eastern Inner Mongolia were dominated by browning pixels. Both the CV NDVI results and NDVI slope results were consistent with previous studies derived from SPOT, MODIS, and GIMMS NDVI [44,45,66]. Furthermore, the rank of CV NDVI among different NNRs in descending order was FEP, WAP, IWP, GMP, DEP, WVP, and PRP (see Table 6).…”
Section: Effects Of National Nature Reserves On Grasslandssupporting
confidence: 89%
See 1 more Smart Citation
“…In addition, our results also showed that the greening pixels were located mainly in the northeast and southwest, whereas central and eastern Inner Mongolia were dominated by browning pixels. Both the CV NDVI results and NDVI slope results were consistent with previous studies derived from SPOT, MODIS, and GIMMS NDVI [44,45,66]. Furthermore, the rank of CV NDVI among different NNRs in descending order was FEP, WAP, IWP, GMP, DEP, WVP, and PRP (see Table 6).…”
Section: Effects Of National Nature Reserves On Grasslandssupporting
confidence: 89%
“…In this study, the MOD13Q1 NDVI was obtained from the Google Earth Engine for the period from 2000 to 2020 in the growing season ranging from April to October. April to October was considered the growing season for the IMAR, as previous research has noted that the vegetation in the IMAR reinvigorates in April and languishes in October [43,44]. In order to assure the reliability of the pixels, we have used the summary QA band to filter the growing season images, leaving only the remote sensing images with confidence.…”
Section: Remotely Sensed Datasetsmentioning
confidence: 99%
“…In addition, as Inner Mongolia is a major livestock province in China, the impact of grazing intensity on vegetation change should not be neglected. We chose the number of livestock as a representative driver to examine its influence [55].…”
Section: Introductionmentioning
confidence: 99%
“…Compared with the correlation study of NDVI with mean temperature and precipitation on the annual scale, the response of the NDVI to the temperature and precipitation on the monthly scale could reveal the influence of hydrothermal changes on the NDVI more deeply (Pei et al, 2019;Guo et al, 2020). On the one hand, the annual-scale dependency between the NDVI and climate factors reflects the long-term change trend relationship between the two, which failed to "peel off" other factors, such as urbanization, land utilization/change, and solar radiation in the course of the year, which affect vegetation.…”
Section: Response Of Normalized Difference Vegetation Index To Climatmentioning
confidence: 99%